Determination of the Optimum Bioconversion Rate of the Composition of Chicken (Gallus gallus) Manure and Fruit Waste Using Black Soldier Fly (Hermetia illucens) Larvae. - Candra Alam (NIM : 11413044), Muhamad
Bioconversion is the process of utilizing waste using biological activity which converts waste into useful materials. The black soldier fly larvae are able to convert organic waste into nutrition in the form of larvae and prepupae which can be used as nutritious rich of protein and fat for chicken, pig, and fish feed. The purpose of this research is to determine the optimum bioconversion rate of organic waste, chicken manure, and fruit waste, using black soldier fly (Hermetia illucens) through the number of feed given and the composition of the feed per larvae per day. This research was conducted through egg hatching phase, larval development phase, and sample testing phase. The given treatment was combinations of two variables, which is the number of feed given and the composition of the feed. The feed given treatment comprised (i) 100% chicken manure; (ii) 75% chicken manure, 25% fruit waste; (iii) 50% chicken manure, 50% fruit waste; (iv) 25% chicken manure, 75% fruit waste; dan (v) 100% fruit waste. The composition treatment comprised (i) 12,5mg/larvae/day; (ii) 25 mg/larvae/day; (iii) 50 mg/larvae/day; (iv) 100 mg/larvae/day, and (v) 200 mg/larvae/day. There were 25 total treatments with 4 repetitions for each treatment. Statistical data processing has undergone two ways analysis of variance (ANOVA) with 95% of confidence level and Duncan test. The research showed that the composition of 75% chicken manure, 25% fruit waste which given 200 mg/larvae/day has the most optimum bioconversion rate with substrate consumption; waste reduction index; efficiency of conversion of digested feed; feeding duration; and development time was 21,63%; 8,49%; 1,53; 14,25 days; and 24,25 days.